ANALISIS KARAKTERISTIK SOSIAL EKONOMI SEBAGAI DASAR PENYUSUNAN STRATEGI PEMASARAN PADA PENGUNJUNG BALIEM CAFE HOTEL HORISON ULTIMA TIMIKA - Natalia Reyne Lumentah; Salsabila Firdausi (Delilah Tinggi Ilmu Ekonomi Jambatan Bulan, 2022)
This study aims to determine the marketing strategy based on the social and economic characteristics of visitors that can be used by Baliem Cafe Hotel Horison Ultima Timika to increase sales volume. The research method used is descriptive research method. In this study, the data collection methods used were the questionnaire method, the documentation method, and the library method. To find out the marketing strategy based on the socio-economic characteristics of visitors at the Baliem Cafe Hotel Horison Ultima Timika, the analytical instruments used are frequency distribution analysis and SWOT analysis. The results of this study indicate that the marketing strategy based on the socio-economic characteristics of visitors to Baliem Cafe Hotel Horison Ultima Timika lies in quadrant I of the SO strategy, which has alternative strategies such as updating modern and classic designs, improving the quality of live music entertainment, maintaining and maintaining the quality of star service standards 4, increasing menu innovation and creativity